2011
DOI: 10.1095/biolreprod.111.091207
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometric Detection of Cholesterol Oxidation in Bovine Sperm1

Abstract: We report on the presence and formation of cholesterol oxidation products (oxysterols) in bovine sperm. Although cholesterol is the most abundant molecule in the membrane of mammalian cells and is easily oxidized, this is the first report on cholesterol oxidation in sperm membranes as investigated by state-of-the-art liquid chromatographic and mass spectrometric methods. First, oxysterols are already present in fresh semen samples, showing that lipid peroxidation is part of normal sperm physiology. After chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 62 publications
2
56
0
Order By: Relevance
“…Spermatozoa contain high amounts of polyunsaturated phospholipids and cholesterol which make them particularly vulnerable to lipid peroxidation (24,25). However, lipid peroxidation during 5 days liquid storage of boar semen has been found to be low (26), as has the incidence of intracellular reactive oxygen species (ROS) in boar spermatozoa (27).…”
Section: Discussionmentioning
confidence: 99%
“…Spermatozoa contain high amounts of polyunsaturated phospholipids and cholesterol which make them particularly vulnerable to lipid peroxidation (24,25). However, lipid peroxidation during 5 days liquid storage of boar semen has been found to be low (26), as has the incidence of intracellular reactive oxygen species (ROS) in boar spermatozoa (27).…”
Section: Discussionmentioning
confidence: 99%
“…A mixture of authentic PI and PS standards was used to correct for ionization and fragmentation efficiencies (23). Cholesterol was quantified as described previously, using deuterated cholesterol (Avanti Polar Lipids) as an internal standard (24).…”
Section: Methodsmentioning
confidence: 99%
“…A study of the impact of oxidative stress on sperm-oocyte fusion has shown a biphasic response depending on the levels of oxidants [73] . Some authors demonstrated that at low level of oxidative stress spermoocyte fusion rates were increased supporting the hypothesis which suggests the role ROS play in activation of the tyrosine phosphorylation events that occur during sperm capacitation [74] and the importance of sterol oxidation in driving the efflux of cholesterol from sperm plasma membrane [75]. Conversely, at higher levels of oxidative stress, lipid peroxidation was induced in the plasma membrane and sperm-oocyte fusion was impaired, probably as a result of damage to acrosome which is involved in the fusion process between spermatozoa and oocytes [76].…”
Section: Oxidative Stress and Sperm Functionmentioning
confidence: 79%